Formulation Food Bars Made From Sago, Cakalang Fish Flour And Puree Mulu Bebe Bananas - Yasim, Fardiana; Muhamad Saleh, Erna Rusliana; Albaar, Nurjanna (Agrikan Jurnal Agribisnis Perikanan, 2022)
This study aimed to influence of sago consentration, fish flour and mulu bebe banana on physical, chemical, organoleptic characteristics and the best formulation of food bars as emergency food. The parameters observed were physical and chemical characteristics include color, texture, moisture content, ash content, carbohydrate, protein, fat, caloric, and organoleptic value.The results showed that food bars from sago, cakalang fish flour and puree mulu bebe banana which hardness level 4,78 N to 7,17 N, color values ​​include color values ​​(L*) 53.28 to 57.76, color value (a*) 8,54 to 10,18, color value (b*) 25,22 to 27,44, moisture content 5,32% to 7,03%, ash content 1,16% to 1,3367 %, protein content 18,44% to 18,72%, fat content 14,34% to 15,78%, carbohydrate content 58,04% to 59,96%, calorific value 438,67 kcal/100 g to 447, 87 kcal/100 g. Organoleptic characteristics includes colors 6,67 to 6,93 (somewhat like), flavor 6,0 to 6,9 (somewhat like), taste 5,92 to 6.723 (neutral to somewhat like) and texture6.0 to 6,8 (somewhat like). The best formulation is that F3 treatment has chemical characteristics includes 6,85% moisture content, 1,26% ash content, 18,48% protein content, 14,34% fat, 58,95% carbohydrate, 438,67/100g calorific value. Physical characteristics includes hardness level of 5,18 N, brightness value (L*) 55.26, redness value (a*) 9,48, yellowish value (b*) 27.01, and organoleptic characteristics include color 6,8 (somewhat likes), flavor 6.0 (somewhat likes), taste 6,18 (somewhat likes), texture 6,0 (somewhat likes)